2020
DOI: 10.7759/cureus.10131
|View full text |Cite
|
Sign up to set email alerts
|

A Challenging Case of Lemierre’s Syndrome With Central Nervous System Involvement and a Comprehensive Review

Abstract: Lemierre’s syndrome (LS) is a complex medical condition that is characterized by an acute oropharyngeal infection leading to thrombophlebitis of the internal jugular vein and an eventual metastatic spread to distant vital organs. This metastatic spread is from septic emboli and is most frequently seen in the lungs, kidneys, and large joints. Central nervous system (CNS) involvement in LS is extremely rare, and only a few cases of CNS involvement have been reported in the literature. For all cases of LS, early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…A more recent case was published of a 28-year-old female with pelvic peritonitis without thrombophlebitis due to F. necrophorum , however of unclear source [9] . Ocular and central nervous system manifestations of the syndrome has also been described [10] , [11] . On our literature review, there has been no prior report of atypical Lemierre syndrome resulting from Bartholin gland infection.…”
Section: Discussionmentioning
confidence: 97%
“…A more recent case was published of a 28-year-old female with pelvic peritonitis without thrombophlebitis due to F. necrophorum , however of unclear source [9] . Ocular and central nervous system manifestations of the syndrome has also been described [10] , [11] . On our literature review, there has been no prior report of atypical Lemierre syndrome resulting from Bartholin gland infection.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the duration of antibiotics, Riordan, 2007, referenced an estimate of 9 to 84 days with an average of 42 days [2]. We have analyzed 26 cases of LS from 2016 to 2021, and the average antibiotics duration was 5.3 weeks (Table 2) [4,17,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][42][43][44]. In clinical practice, due to the lack of an established guideline, the duration and selection of antibiotics highly varied based on clinical responses in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Tis perspective is also refected in the only retro-perspective study available that studied about 700 cases of LS from 2000 to 2017 and concluded that there are no disease-specifc elements of concern regarding the safety of anticoagulation in LS [12]. From our analysis of 26 LS cases from 2016 to 2021, anticoagulation was used in 76% of cases and the average duration was 9.8 weeks (ranging from 1 week to 16 weeks; Table 2 [4,17,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][41][42][43][44]. In our case, due to the absence…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic septic emboli have a long path from the IJV downstream to the CNS contributing to the infrequency of CNS involvement. Patients with Lemierre's experience CNS complications between 1% and 3.6% of the cases [5][6][7] . Because of variability and atypical presentation, the diagnosis and management of Lemierre's can be challenging.…”
mentioning
confidence: 99%
“…One study discussed a patient with Lemierre's who developed hemiplegia after carotid sinus and internal carotid artery involvement 2 . The pathophysiology remains controversial, but usually the initial infection is in the oropharynx and spreads hematogenously to the IJV through the lateral pharyngeal space 5 . Infrequently, Lemierre's can affect the central nervous system (CNS), including epidural and subdural space involvement 3 .…”
mentioning
confidence: 99%